Facilitating Implicit Emotion Regulation in Online News Commenting—An Experimental Vignette Study. Issue 5 (18th February 2023) - Syrjämäki, Aleksi H; Ilves, Mirja; Kiskola, Joel; Rantasila, Anna; Isokoski, Poika; Olsson, Thomas; Surakka, Veikko
Abstract: An online experiment investigated the perceived effects of a user interface (UI) intervention aiming to support online news commenters' emotion regulation. By describing the comment's tone to the user, the expected effect was activation of the implicit emotion regulation process of affect labeling (i.e. naming emotions). The perceived emotion- and behavior-related effects of the labeling intervention were investigated using the experimental vignette methodology. Participants read a vignette describing the behavior of an uncivil commenter and assessed the commenter's probable responses to the labeling intervention or a control intervention shown in the UI. The results showed that, when compared to a control condition, the labeling intervention was assessed to evoke positive emotions and to result in mitigation of uncivil behavior. This suggests that UI solutions that support emotion regulation are a promising approach to reducing uncivil comments that users might afterward regret, and hence potentially improving the quality of online discussions.